Atrioventricular Synchrony Algorithm Modeling of a Leadless Pacemaker Family: A Virtual Patient Analysis - Leal, Miguel A.; Sheldon, Todd; Escalante, Keelia; Holm, Mikayle; Galarneau, Michelle; Stromberg, Kurt; Piccini, Jonathan P. (Cardiovascular engineering and technology, 2025)
Purpose To assess the impact of enhancements to the Atrioventricular Synchrony (AVS) algorithms of a next generation Micra leadless pacemaker (Micra AV2). Methods Accelerometer data were extracted from the AccelAV clinical study and were used to create virtual patients. A series of Monte Carlo simulations were run for each virtual patient to compare an enhanced Atrial Sensing Setup algorithm and Auto + A3 Threshold algorithm vs. original algorithms. A real-world survey was also conducted to observe clinical time savings from AVS programming burden reduction. Results The enhanced Atrial Sensing Setup in Micra AV2 devices demonstrated > 70% AVS in 27 of 30 (90%) patients while 13 of 30 (43%) Micra AV patients had > 70% AVS ( p < 0.001) with no manual programming. The Micra AV2 Auto + A3 Threshold without additional manual programming demonstrated improved overall ambulatory AVS in the 80–100 bpm range (84.1%). Based upon survey results, the enhanced Atrial Sensing Setup algorithm accounted for an estimated reduction in median device check time of 13 min per patient. Conclusions Simulation-based analyses of the Micra AV2 leadless pacemaker projected significant improvements in automatic AVS at high sinus rates and an increase in the number of patients with > 70% AVS without clinician programming. Real-world survey results reported a reduction in device check time with the improvements. Significance: Improvements in the AVS algorithms in Micra AV2 allow for better automatic AVS at higher heart rates and reduced clinic utilization burden.